Sintesis Nanopartikel Cobalt Ferrite (CoFe2O4) dengan Metode Kopresipitasi dan Karakterisasi Sifat Kemagnetannya - Eko Arief Setiadi; Nanda Shabrina; Hesti Retno Budi Utami; Nur Fadhilah Fahmi; Takeshi Kato; Satoshi Iwata; Edi Suharyadi (Department of Physics, Sebelas Maret University, 2016)
Magnetic nanoparticles of cobalt ferrite (CoFe2O4) have been synthesized by co-precipitation method with various synthesis temperature and concentration of NaOH. The structural characteristics and particle size of CoFe2O4 were determined by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM), its showed that nanoparticles well crystallized with various grain size which depend on synthesis parameters. The grain sizes estimated using the Scherrer formula were found that the grain size increased with increasing temperature synthesis and decreasing concentration of NaOH. Magnetic characterization of CoFe2O4 nanoparticles was investigated by using a Vibrating Sample Magnetometer (VSM). Sample with various concentration of NaOH showed that coercivity was decrease with the decrease of particle size. In other hand, samples with various synthesis temperature found that sample withsmallest grain size have high coersivity. The saturation magnetization increase when crystallinity increase. Based on the results, it can be concluded that magnetic characterization of CoFe2O4 was influenced by grain size and crystallinity.